Voluntary modulation of saccadic peak velocity associated with individual differences in motivation. (January 2020) - Muhammed, Kinan; Dalmaijer, Edwin; Manohar, Sanjay; Husain, Masud
Abstract: Saccadic peak velocity increases in a stereotyped manner with the amplitude of eye movements. This relationship, known as the main sequence, has classically been considered to be fixed, although several recent studies have demonstrated that velocity can be modulated to some extent by external incentives. However, the ability to voluntarily control saccadic velocity and its association with motivation has yet to be investigated. Here, in three separate experimental paradigms, we measured the effects of incentivisation on saccadic velocity, reaction time and preparatory pupillary changes in 53 young healthy participants. In addition, the ability to voluntarily modulate saccadic velocity with and without incentivisation was assessed. Participants varied in their ability to increase and decrease the velocity of their saccades when instructed to do so. This effect correlated with motivation level across participants, and was further modulated by addition of monetary reward and avoidance of loss. The findings show that a degree of voluntary control of saccadic velocity is possible in some individuals, and that the ability to modulate peak velocity is associated with intrinsic levels of motivation.